Prevalence, antibiotics susceptibility and genotyping of foodborne bacteria in meat, eggs and feeds from selected markets / Chin Pui San - Chin , Pui San (2017)
Food safety in poultry production industry is a global concern including Malaysia. Antibiotics are used in poultry industry and consequently increases emergence of multidrug resistance foodborne pathogens. A total of 100 non-repeatitive isolates consisting 38 isolates of Salmonella spp., 28 isolates of Listeria spp., 20 isolates of Escherichia coli and 3 isolates of Staphylococcus aureus were isolated from 50 sample of chicken meat, 40 eggs and 10 types of feeds obtain from selected local markets in Klang Valley, Malaysia from 2015 to 2016. This study was aimed to assess the prevalence, antimicrobial susceptibility and genotypes of bacteria isolates. Resistance was most frequently detected to erythromycin (100%), followed by to tetracycline (76%), azithromycin (58%), streptomycin (24%), ampicillin (18%), chloramphenicol (18%), trimethoprim (18%), nalidixic acid (18%), gentamicin (13%), ciprofloxacin (5%) and nitrofuratoin (5%) in 38 Salmonella isolates. For the 28 Listeria isolates were highly resistant to clindamycin (89%), followed by tetracycline (86%), ceftriaxone (75%), ampicillin (64%) and penicillin G (50%). Thirty-five of Salmonella (92.1%, 35/38) isolates were resistant to at least two antibiotics, 14 (36.8%, 14/38) at least to four antibiotics, and 4 isolates (10.5%, 4/38) showed 8 multiple antibiotic resistance against 19 different antibiotics. For the 27 (96.4%, 27/28) Listeria isolates were resistant at least to two antibiotics, of which 11 isolates (39.3%, 11/28) showed 5 multiple antibiotic resistance against 11 different antibiotics in the study. Pulse-Field Gel Electrophoresis (PFGE) generated 6 major clusters with 12 patterns and 7 patterns in Salmonella and Listeria isolates. Salmonella and Listeria isolates clustered under similar PFGE patterns were resistant to similar categories of antibiotics. Of these, tetA, tetB, sul1, sul2, qnrS, qnrB and mphA and invA were detected in 25 (66%), 2 (5%), 20 (53%), 38 (100%), 24 (63%), 2 (5%), 4 (11%) and 38 (100%) Salmonella isolates using Polymerase Chain Reaction (PCR). Subsequently, the draft genome of 4 selected Salmonella spp. were sequenced using HiSeq 2000 Illumina platform and antibiotic resistance genes were annotated using RAST (Rapid Annotation using Subsystem Technology). The findings showed that chicken breast fillet is a potential source of antibiotic-resistant Salmonella and Listeria species. Majority of Salmonella and Listeria species isolated from meat were multidrug resistant and pose great potential hazard to public health and food safety.